(3GdacQ GdaQfSj GdeYGUQ (B/s - (3ehQhSjQ, EOhGQs; (3YGOds ((3HjQhJ(B. (3HGQjS (B:s (3efThQGJ YhjOGJ ,s, 1978)
(3GdMQH GdYGdejI GdKGfjI h GdGTJOGOGJ GdKbGajI(B, (3GdGfJbGO GdhLhOj(B, (3JacjQ aj GddZI h GdCOH(B, (3GdJHQjQ GdGfJbGOj eWHbG Ydi GdJLQHI GdCNdGbjI hGdMjGI GdSjGSjI(B, (3GdKbGaI GdaQfSjI hGdeGQcSjI(B, (3eMGhdGJ GdGHSJehdhLjI GdHfjhjI(B, (3KhQI GdacQ GdOjfj Gddg h GdKbGaIs
(3eJQLes
Keywords: (3GdKbGaI GdaQfSjIs; (3GdacQ GdaQfSjs